A re-examination of information seeking behaviour in the context of activity theory - Wilson T.D. (Information Research: An International Electronic Journal)
Introduction. Activity theory, developed in the USSR as a Marxist alternative to Western psychology, has been applied widely in educational studies and increasingly in human-computer interaction research. Argument. The key elements of activity theory, Motivation, Goal, Activity, Tools, Object, Outcome, Rules, Community and Division of labour are all directly applicable to the conduct of information behaviour research. An activity-theoretical approach to information behaviour research would provide a sound basis for the elaboration of contextual issues, for the discovering of organizational and other contradictions that affect information behaviour. It may be used to aid the design and analysis of investigations. Elaboration. The basic ideas of activity theory are outlined and an attempt is made to harmonize different perspectives. A contrast is made between an activity system perspective and an activity process perspective and a diagrammatic representation of the process perspective is offered. Conclusion. Activity theory is not a predictive theory but a conceptual framework within which different theoretical perspectives may be employed. Typically, it is suggested that several methods of data collection should be employed and that the time frame for investigation should be long enough for the full range of contextual issues to emerge. Activity theory offers not only a useful conceptual framework, but also a coherent terminology to be shared by researchers, and a rapidly developing body of literature in associated disciplines.